ERWP 2021
DOI: 10.24148/wp2021-05
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Status of People with Disabilities and their Families since the Great Recession

Abstract: People with disabilities face substantial barriers to sustained employment and stable, adequate income. We assess how they and their families fared during the long economic expansion that followed the Great Recession of 2007-09, using data from the monthly Current Population Survey (CPS) and the March CPS annual income supplement. We find that the expansion bolstered the well-being of people with disabilities and in particular their relative labor market engagement. We also find that applications and awards fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…However, labor market conditions may change over time for individuals with different educational attainment. The slight decline in IRR during our study period is consistent with the flattening or even decline in college wage premiums in recent decades (Ashworth & Ransom, 2019; Bengali et al, 2023). Autor, Dube, and McGrew (2023) found that labor market tightness following the height of the COVID-19 pandemic spurs real wage growth for the lowest earning quartile of workers, leading to compassion in the wage distribution.…”
Section: Summary and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, labor market conditions may change over time for individuals with different educational attainment. The slight decline in IRR during our study period is consistent with the flattening or even decline in college wage premiums in recent decades (Ashworth & Ransom, 2019; Bengali et al, 2023). Autor, Dube, and McGrew (2023) found that labor market tightness following the height of the COVID-19 pandemic spurs real wage growth for the lowest earning quartile of workers, leading to compassion in the wage distribution.…”
Section: Summary and Discussionsupporting
confidence: 85%
“…This time frame is significant, as it coincided with economic growth and a tightening labor market in the aftermath of the 2008 Great Recession. Recent research indicates a stagnation or even decline in college wage premiums after the Great Recession (Bengali et al, 2023). Similarly, Ashworth and Ransom (2019) found that the increasing college wage premium for the 1950–1970 birth cohort was followed by a flattening for the 1980–1984 birth cohort.…”
Section: Literature Reviewmentioning
confidence: 99%